Gods in Thai Literature: Role of Creator and Destroyer - พูลพิพัฒน์ นราวัลย์ (Ganesha Journal, 2019)
This research aimed to study the origin and characteristics of gods in Thai literature, and analyze roles of god as creator and destroyer. The samples included 4 topics of Thai literatures including gods as actors, namely, Ramayana written by King Rama I, Origin of Ramayana and Ten Incarnations of Narai written by King Rama VI, and Illarach Verse of Phraya Si Sunthorn Wohan (Pun Salak). The data were collected by using form for recording statement or conversation of the 3 gods to analyze their behavior to see if they were creator or destroyer and in what way. The findings revealed that Brahma had come up as god with four faces and four hands, with red skin, had good heart and kindness, and had been widely respected. Shiva had come up as Yogi with one face with 2 or 10 hands of certain postures, with white skin. Shiva had good heart but easily overwhelmed by praise. The god would easily bless. Narayana came up as good looking god with one face and four hands. Skin of Narayana could change according to each period. Narayana comes up to protect the world with high power. Brahma had the roles of creator who was indifferent, self-sufficient, sacrifice, kind, and giver. Shiva had the role of a giver, being responsibility, planners, keeping contract, praising others, and maintain relationship. Narayana had the roles in suppressing sufferings of other, serving others, having tricks to do things, being forgiver, having self-pride, and being reasonable. Roles of the 3 gods as creators and destroyers had practiced along one’s rights and status along his/her beliefs and perception of the society which contended that Brahma was the creator, Shiva – the destroyers, and, Narayana the world protector. Other roles having been analysed were the roles actually taken which were congruent or incongruent to the roles in which people believe for perceive.